Motor efficiency in Relation to Body Weight Status and Gender in Preschool Children - Miran Muhič (University of Maribor Press, 2024)
Deficits in motor skills and function are associated with overweight and obesity in children. This study aimed to investigate the development of motor efficiency in 3-4-year-old children over seven months and to identify possible gender and body weight status differences in motor efficiency. In the study, there were 45 children (21 girls, 24 boys), the mean age of whom was 39 months. Analysis of the results of testing for differences in motor efficiency according to body weight status and movement components showed no statistically significant differences (p>0.05) between healthy weight and overweight children.